2016
DOI: 10.1007/s12020-016-1028-0
|View full text |Cite
|
Sign up to set email alerts
|

The changing faces of corticotroph cell adenomas: the role of prohormone convertase 1/3

Abstract: The spectrum of corticotroph cell adenomas is very wide. Though rarely, silent corticotroph cell adenomas (SCA) may transform into corticotroph cell adenomas associated with Cushing's disease (CD). The aim of the study was to investigate the role of prohormone convertase 1/3 (PC1/3) in the transformation of SCA into CD. We reviewed the records of 1259 consecutive endoscopic endonasal procedures for pituitary adenomas from 1998 to 2013. Of these, 132 were CD and 44 were SCA. During the follow-up, three patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…For these cases, we retrieved clinical information from the last follow-up, dating at the time of publication, with the same methods applied to the investigation of new cases (see 'Materials and methods' section). For all cases, histological and radiological revision was performed applying the criteria suggested by Trouillas' et al (9,10,11,12).…”
Section: Study Samplementioning
confidence: 99%
“…For these cases, we retrieved clinical information from the last follow-up, dating at the time of publication, with the same methods applied to the investigation of new cases (see 'Materials and methods' section). For all cases, histological and radiological revision was performed applying the criteria suggested by Trouillas' et al (9,10,11,12).…”
Section: Study Samplementioning
confidence: 99%
“…The most studied hypothesis relates to the post-transcriptional regulation of POMC and post-translational regulation of ACTH. Some authors (8,9,10,11,12) have suggested that the transcription factors and convertases involved in the processing of POMC and degradation of ACTH are implicated in the lack of secretory activity that gives rise to the absence of Cushing's disease. TBX19 (Tpit) and NEUROD1 are transcription factors expressed in CT cells that contribute to the corticotroph-specific POMC transcription (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The proconvertase PC2, encoded by the PCSK2 gene, is an endoproteolytic enzyme responsible for the processing of biologically active ACTH. Unlike PC1/3, PC2 is only present in the intermediate lobe pituitary cells, where it processes mature ACTH (1-39) to produce corticotropin-like intermediate lobe peptide (CLIP) and a smaller ACTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) peptide (16,17). Finally, the ACTH fragments are cleaved to deacetyl alpha-MSH (da-MSH) by carboxypeptidase E (CPE) and PAM (13).…”
Section: Introductionmentioning
confidence: 99%
“…A large single-centre retrospective cohort of surgically resected NFpitNETs (n = 124) over 10 years reported that 11% of sSAs and 5.6% of sCAs converted to functional adenomas during follow-up (Langlois et al 2017). In another study, 3.9% of sCAs switched to Cushing's disease in a transformation time of 1-7 years (Righi et al 2017). Thus, close monitoring of such NFpitNETs is recommended not only because of their high risk of recurrence but also due to the risk of becoming functional over time.…”
Section: Natural Historymentioning
confidence: 99%